2020
DOI: 10.1021/acs.iecr.0c02940
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Cell-Catalyzed Synthesis of Phenolic Glycoside Esters, and Their Antioxidant and Antimelanogenic Properties

Abstract: Phenolic glycosides are the major secondary metabolites of plants, which exhibit multiple attractive biological and pharmacological activities. In this study, we developed a new and efficient method for acyl modification of phenolic glycosides by using whole-cell biocatalysts, aiming to improve their liposolubility and bioactivities. Using resveratrol, salidroside, piceid, and phlorizin as substrates, the substrate recognition characteristics of Candida parapsilosis were studied and salidroside showed the high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…Cell culture methods are in accordance with the literature. 48 Briefly, B16 mouse melanoma cells were cultured in Dulbecco's modified Eagle's medium (DMEM) supplemented with 1% penicillin/ streptomycin and 10% fetal bovine serum solution in a humidified incubator with 5% CO 2 at 37 °C. After the cells had grown to 85− 90% confluence, they were harvested and seeded at the appropriate number counted with a hemocytometer into wells of cell culture plates for further experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell culture methods are in accordance with the literature. 48 Briefly, B16 mouse melanoma cells were cultured in Dulbecco's modified Eagle's medium (DMEM) supplemented with 1% penicillin/ streptomycin and 10% fetal bovine serum solution in a humidified incubator with 5% CO 2 at 37 °C. After the cells had grown to 85− 90% confluence, they were harvested and seeded at the appropriate number counted with a hemocytometer into wells of cell culture plates for further experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Cell culture methods are in accordance with the literature . Briefly, B16 mouse melanoma cells were cultured in Dulbecco’s modified Eagle’s medium (DMEM) supplemented with 1% penicillin/streptomycin and 10% fetal bovine serum solution in a humidified incubator with 5% CO 2 at 37 °C.…”
Section: Methodsmentioning
confidence: 99%
“…Acylation is an effective approach to improve the bioactivity and liposolubility of phenolic glycosides. 17,18 Previous studies showed that arbutin laurate had higher antioxidant activity than arbutin itself against the oxidation of linoleic acid, 19 and acetylated arbutin strongly inhibited B16 mouse melanoma cell migration in a dose-dependent manner, which was not possessed by arbutin itself. 20 These findings further promoted researchers in developing new methods for the preparation of arbutin esters.…”
Section: Introductionmentioning
confidence: 99%